The Contribution of Internal and External Supervision to School Performance - Muhammad Arifin (EDUTECH, 2020)
This research aims to figure out the contribution of internal control to the school performance, the contribution of external control to the school performance, and the contribution of internal and external control to the school performance. This study applies the descriptive research to find out the contribution among the variables of the research. The population of this study is all the 488 teachers of SMP Negeri in Binjai. The sample is 10 percent of population that is 49 teachers. The instrument used to collect the data is Likert scale questionnaire. The techniques of data collection are correlation analysis, simple and double regression and partial correlation. The linearity test between the internal control(X1) to the school performance (Y), the external control (X2) to the school performance (Y) have correlation each other and show independent, from significant score with Ftest and Ttest, if it is significant with 0,05. The findings of this research show that there are positive contribution and the significant among the internal control variable (X1) to the school performance (Y) as 40,1 %. There are positive and significant contribution among external control variable (X2) to school performance (Y) as 50,4 % and the internal control contribution (X1) as well as External control (X2) to the school performance (Y) as 56,7 % and the rest is 43,3% from other variables that are not included in the study variable in this study. The conclusions are internal control to the teachers conducted by principal and external control conducted by school committee contributed to school performance in effective school management.